Pengaruh Locus of Control Terhadap Perilaku Impulsive Buying Pada Mahasiswa Pengguna Fitur Online Live Streaming Media Sosial - Fitri, Rahmi; Rusli, Devi (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
The aim of this research is to examine the influence of locus of control in the formation of impulsive buying behavior in students at Padang State University aged 18-25 years. The total sample amounted to 239 people using random sampling techniques. Data collection used a locus of control measuring instrument which was prepared based on aspects of Levenson (1974) by Putri (2021) and an impulsive buying measuring instrument which was compiled based on aspects by Verplanken and Herabadi (2001). There is an influence between locus of control on impulsive buying behavior with a value of r = 0.278 and P = 0.000 (p <0.01), indicating that there is a significant positive influence between locus of control on impulsive buying behavior in students who use online live streaming social media features and the influence between variables when measured was 7.8%. The benefits of research are to understand the influence of behavioral control in adapting to increasingly rapid technological developments, one of which is in shopping features and recognizing the decision control of students and students in the dominance of orientation in determining the behavior to be carried out.